2019
DOI: 10.12688/f1000research.19197.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding dengue

Abstract: This is a selective review of recent publications on dengue clinical features, epidemiology, pathogenesis, and vaccine development placed in a context of observations made over the past half century. Four dengue viruses (DENVs) are transmitted by urban cycle mosquitoes causing diseases whose nature and severity are influenced by interacting factors such as virus, age, immune status of the host, and human genetic variability. A phenomenon that controls the kinetics of DENV infection, antibody-dependent enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 136 publications
(135 reference statements)
3
62
0
10
Order By: Relevance
“…Secondary heterotypic dengue infection has been associated with severity due to the ineffective viral control of preexisting cross-reactive and low-affinity memory T cells (62). However, the risk of severe dengue in secondary heterotypic infection was not high in our studies (45,49) including the current study and some others (62). We have also analyzed T cell kinetics in the context of primary and secondary infection (Supplementary Figures 4A, B).…”
Section: Discussionmentioning
confidence: 75%
“…Secondary heterotypic dengue infection has been associated with severity due to the ineffective viral control of preexisting cross-reactive and low-affinity memory T cells (62). However, the risk of severe dengue in secondary heterotypic infection was not high in our studies (45,49) including the current study and some others (62). We have also analyzed T cell kinetics in the context of primary and secondary infection (Supplementary Figures 4A, B).…”
Section: Discussionmentioning
confidence: 75%
“…1. Clinical and epidemiological studies report the association of second heterotypic dengue infections as well as primary dengue infections in infants of dengue-immune mothers with dengue vascular permeability syndrome (DVPS) [20][21][22].…”
Section: Pathogenesis Of Denguementioning
confidence: 99%
“…Studies have shown that cytokine rise at presentation may indicate whether a patient is likely to develop severe dengue or not [133,134]. NS1-mediated cytokine release can be inhibited by TLR4-antagonist LPS-Rhodobacter sphaeroides, a gram-negative facultative photosynthetic bacterium which can lead to targeted therapy in future [22]. Another study has shown interest in the use of serum chymase levels as a predictive biomarker of DHF.…”
Section: Recent Insights Into Dengue Pathogenesis and Biomarkersmentioning
confidence: 99%
“…DENV consists of a genome approximately 11kb nucleotides (nt) in length. The genome encodes three structural proteins, nucleocapsid (C), precursor membrane (prM) and envelope (E), as well as seven nonstructural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%